Second International Meeting for Applied Geoscience &Amp; Energy 2022
DOI: 10.1190/image2022-3744978.1
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Marchenko imaging with distance-aware matrix reordering, tile low-rank compression, and mixed-precision computations

Abstract: A variety of wave-equation-based seismic processing algorithms rely on the repeated application of the Multi-Dimensional Convolution (MDC) operator. For large-scale 3D seismic surveys, this comes with severe computational challenges due to the sheer size of high-density, full-azimuth seismic datasets required by such algorithms. We present a three-fold solution that greatly alleviates the memory footprint and computational cost of 3D MDC by leveraging a combination of i) distance-aware matrix reordering, ii) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This ultimately leads to a faster and less memory demanding MDD process. This corroborates our previous findings in the context of Marchenko-based redatuming for a synthetic dataset modelled in a much simpler geological setting (Hong et al, 2021;Ravasi et al, 2022a).…”
Section: Introductionsupporting
confidence: 91%
“…This ultimately leads to a faster and less memory demanding MDD process. This corroborates our previous findings in the context of Marchenko-based redatuming for a synthetic dataset modelled in a much simpler geological setting (Hong et al, 2021;Ravasi et al, 2022a).…”
Section: Introductionsupporting
confidence: 91%
“…Our MP TLR-MVM implementation renders SRI competitive with industry standard methods from a computational point of view, and therefore attractive in practice. Related work (Ravasi et al, 2022) has recently shown the versatility of our approach and its applicability to other geophysical problems. However, whilst Ravasi et al (2022) are mostly concerned with the geophysical aspects of the problem, our article focuses on detailing the implementation of our synergistic MP TLR-MVM approach as well as providing an extensive suite of performance benchmarks.…”
Section: Related Workmentioning
confidence: 97%